Transcriptional landscape of macrophages in cutaneous graft-versus-host disease - Döbel, Thomas; Schäkel, Knut (British journal of dermatology, 2024)
Graft-versus-host disease (GvHD) is a common and life-threatening immunological response after haematopoietic stem cell transplantation. Skin is one of the most frequently affected organs and cutaneous GvHD has gained considerable research attention. Because alloantigen-specific immunity is at the core of GvHD, a main focus of past research was on alloreactive CD4 and CD8 T cells.1 However, T-cell responses are directed by antigen-presenting cells such as mononuclear phagocytes (MNPs), making these cells important players in GvHD.2 Strobel et al. present one of the first studies to investigate changes in the macrophage compartment in cutaneous GvHD.3 MNPs, which are present in every layer of the skin, are sensitive to changes in the tissue microenvironment, and also guide and instruct local innate and adaptive immune responses.4,5 Therefore, investigation of the MNP compartment in GvHD could potentially shed light on important feedback mechanisms.
Gesehen am 03.05.2024
Editorial Material